Pricing policies for public enterprises - Webb, Michael Gordon (London : Macmillan, 1976)
This book deals with the appropriate pricing of the products of public enterprises that have been of interest to engineers and public administration.
Bibliography: p. 92-[96].
oo 16/10/18
Loans
Keywords: Pricing; Government business enterprises